Knowledge, Attitudes, and Practices of Hand Hygiene, Mask Use, and Social Distancing among Public Hospital and Polyclinic Nurses in Barbados during the Coronavirus 2019 Pandemic - Uma Gaur; Wendy Sealy; Ambadasu Bharatha; Natasha P. Sobers; Kandamaran Krishnamurthy; Michael H. Campbell; Cara Cumberbatch; Maia Drakes; Marielle Gibbs; Charisse Alexander; Heather Harewood; O. Peter Adams; et al. (MDPI AG, 2024)
Background: Nurses are essential members of the healthcare workforce and were among the first-line carers for patients in community and hospital settings during the COVID-19 pandemic. As a result, they were at a heightened risk of infection, resulting in several reported deaths among nursing staff. Several preventive measures were adopted to contain the spread of the COVID-19 virus. This study aims to explore the knowledge, attitudes, and practices (KAP) of nurses regarding hand hygiene, mask wearing, and social distancing measures in healthcare settings in Barbados during the COVID-19 pandemic. Method: An online survey of nurses working in public hospitals and polyclinics (public primary care clinics) in Barbados from March 2021 to December 2021 was conducted. A nonsystematic convenience sampling method was employed to recruit nurses who were readily available and willing to participate. A questionnaire captured the sociodemographic information and knowledge and practices related to hand hygiene, the use of face masks, and social distancing. Each correct response received one mark. Overall knowledge scores were categorized as poor (<60%), average (60-80%), or good (>80-100%). Results: Of the 192 participants, the majority were female (82.8%) and had >5 years of experience (82%). The findings revealed that 45.8% had poor knowledge of hand hygiene, and that the knowledge of 43.8% of respondents was average. Multivariable logistic regression showed that, after adjustment for age and gender, registered nurses had 2.1 times increased odds (95% confidence interval 1.0, 4.2) of having good knowledge compared to other nursing categories. Regarding mask wearing, 53.6% of nurses had average knowledge, and 27.1% had good knowledge. Multivariable logistic regression showed that, after adjustment for age and gender, registered nurses had 3.3 times increased odds (95% confidence interval 1.5, 7.4) of having good knowledge compared to nursing assistants. A total of 68.6% of respondents followed the correct steps of handwashing every time, and 98.3% wore a mask in public places. More than half of the nurses (51.2%) kept a safe distance from others to avoid spreading SARS-CoV-2; one-third were in a crowded place(s) in the past three months, and 55.8% usually followed guidelines for social isolation as recommended by the WHO. Conclusions: The study identified knowledge deficiencies related to hand hygiene and wearing masks among nurses. It is imperative to provide additional training on infection control measures.